Demanding clients state their case: Comments on the client round table at La Rochelle (SFT universite d'ete, July 2002) - Durban, Chris (The Journal of Specialised Translation, 2004)
Linguists are as vulnerable as the most hapless monolingual buyer of translation when a debate takes place in a language they do not speak or read. The author draws reader's attention to a discussion of translation quality and priorities by three demanding buyers of financial translation, and highlights issues that might be of interest to students, teachers and practicing translators. The text of the round table can be accessed in French at http://www.sft.fr/dossiers/actesrochelle/8acheteurs.pdfStandard features of contributions to translator egroups and bulletin boards are gloomy references to relentless pressure on prices and killer deadlines. Articles by academics, too, often include a negative reference to the marketplace and its impact on quality.Meanwhile specialised translators are demanding and collecting comfortable fees while interacting with premium clients who insist on top-notch quality and show genuine appreciation for their efforts. Perhaps these translators are too busy working to spread the word; perhaps they simply do not identify with the hand wringing. Otherwise they might speak up to remind newcomers to the profession and some of the ageing nay sayers that the situation is not all that bleak.[1]In any event, public discussions of translation priorities by demanding clients in this segment of the market are rare enough to merit greater exposure. In July 2002, the French national translators' association SFT (Société française des traducteurs) sponsored a three-day "université d'été de la traduction financière" in La Rochelle, France. At the closing session, three translation consumers — Edouard Manset of CIC Asset Management, Jean Rodriguez of the European Central Bank press office, and Antoine Getten of Paris-based translation company Translations — set out their priorities and discussed how expert translators serve them.In the following summary, the author (who was also the round table moderator) draws readers' attention to this discussion of criteria for excellence in the translation of financial texts, and highlights issues that might be of interest to students, teachers and practising translators complete transcript, both of this round table and of other conference presentations, some in English, some in French — can be downloaded from the SFT website [www.sft.fr/Dossiers/index.html]).